Improvement of luminous efficiency using LI-doped MgO layer coated by MgCaO crystal powders in plasma display panels. (4th March 2017) - Park, Choon-Sang; Jung, Eun Young; Tae, Heung-Sik
ABSTRACT: In this study, the influences of the Li-doped MgO layer sprayed by MgCaO crystal powders on the discharge and luminous efficiency characteristics are examined under the high Xe (= 30%) gas condition in 6-in. test alternating-current plasma display panels (ac-PDPs) with 50-in. full-high definition (FHD) cell size. Our experimental results reveal that spraying the MgCaO crystal powders on the Li-500 ppm doped MgO layer can reduce the firing voltage considerably by about 60 V under the high Xe (= 30%) gas condition. As a result, the maximum luminous efficacy of about 40% improvement is obtained when adopting the Li-500 ppm doped MgO layer coated by MgCaO crystal powders under high Xe (= 30%) gas condition.